2012
DOI: 10.1007/s00264-011-1396-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of cementless femoral reconstruction following intertrochanteric osteotomy

Abstract: Purpose The objective of this retrospective cohort study was to assess the long-term outcome of cementless femoral reconstruction in patients with previous intertrochanteric osteotomy (ITO). Methods We evaluated the clinical and radiographic results of a consecutive series of 45 patients (48 hips, mean age 50 years) who had undergone conversion hip replacement following ITO with a cementless, grit-blasted, doubletapered femoral component. Clinical outcome was determined using the Harris hip score. Stem surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…In this study, prior DHS-treated patients receiving CTHA tended to have less resistance to periprosthetic fractures. One of the major reasons for this finding might be that the patients sustaining stable intertrochanteric fractures treated with a DHS tended to have poorer bone quality caused by stress shielding, which was in line with the prior consensus that a high incidence of mechanical complications (periprosthetic fractures) was recorded in patients who had received prior DHS treatment [7, 9, 16, 24]. As demonstrated by recent biomechanical testing [19], patients undergoing DHS may have poorer bone quality caused by stress-shielding than patients undergoing PFNA, which might partly explain the destruction of the bone and the disuse and atrophy of the proximal femur.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In this study, prior DHS-treated patients receiving CTHA tended to have less resistance to periprosthetic fractures. One of the major reasons for this finding might be that the patients sustaining stable intertrochanteric fractures treated with a DHS tended to have poorer bone quality caused by stress shielding, which was in line with the prior consensus that a high incidence of mechanical complications (periprosthetic fractures) was recorded in patients who had received prior DHS treatment [7, 9, 16, 24]. As demonstrated by recent biomechanical testing [19], patients undergoing DHS may have poorer bone quality caused by stress-shielding than patients undergoing PFNA, which might partly explain the destruction of the bone and the disuse and atrophy of the proximal femur.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, in China, 70% of surgeons prefer PFNA over DHS for treating a stable intertrochanteric fracture in active elderly patients [10]. Other studies have previously reported that DHS was the best choice for the initial treatment of stable intertrochanteric fractures [6, 7, 9, 16, 17]. Although the complication rates of DHS devices ranged from 12 to 34% [10], DHS was still regarded as a preferred device for stable intertrochanteric fractures in active elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common intraoperative complications were femoral fractures, which typically were fixed with either screws or wiring except for two hips reported by Merle et al [18] and four of five hips in the study by Søballe [27], which were left untreated. Other intraoperative complications were difficulties in hardware removal and nerve palsy: five studies reported the occurrence of nerve palsy, whereas in the other 10 no nerve palsies occurred.…”
Section: Complicationsmentioning
confidence: 92%